Anatomical and Histological Evaluation of Novel PLA-Keratin Bio-Composite Scaffolds for Tissue Engineering Applications - Srinath R. D.; Ganga Naik S.; Dhoolappa M.; Girish M. H.; Girish Kumar V.; Prasad R. V. (Indian Journal of Veterinary Anatomy, 2025)
Keratin, a natural protein extracted from poultry feathers, has gained significant interest in biomedical applications due to its biocompatibility, bioactivity, and ability to support cell growth. However, its large-scale utilization is limited by extraction challenges. In this study, keratin was successfully extracted from chicken feathers using a reductive method involving sodium metabisulfite, SDS, and urea, followed by dialysis and lyophilization. Biocomposite scaffolds were fabricated by solvent casting using polylactic acid (PLA) andvarying concentrations of keratin. Subcutaneous implantation of PLA and PLA-keratin composites was performed in Sprague Dawley rats for 7, 14, and 28 days to assess biocompatibility and biodegradability. Histological analyses showed minimal inflammation and favorable tissue integration in all groups, with PLAkeratin scaffolds exhibiting increased cellular infiltration without adverse responses. The addition of keratin did not significantly alter fibrous tissue encapsulation but enhanced cellular response, indicating promising potential for tissue engineering. This simple and scalable method for keratin extraction and scaffold fabrication offers a viable approach to developing biodegradable, bioactive materials combining the mechanical strength of PLA with the biological functionality of keratin.